Caracterização de um modelo de sinucleinopatia induzida por LPS: investigação de alterações nas vias do inflamassoma e das chaperonas - Bárbara Zuccolotto Schneider Guimarães Parreira (2024)
ABSTRACT Introduction: Synucleinopathies are a set of neurodegenerative disorders characterized by the accumulation of toxic aggregates of the alpha-synuclein protein in the central nervous system, with Parkinson's Disease (PD) being the most prevalent among them. Investigating the prodromal phase of PD is of great relevance, considering that this phase occurs prior to classic nigro-striatal neurodegeneration. The continuous activation of the inflammasome — a protein complex involved in the regulation of the innate immune response — is associated with neurodegenerative disorders and its deregulation can also alter the chaperone pathway, a set of cytoplasmic proteins that play a central role in maintaining cellular proteostasis. Recent studies highlight that the network of connections between chaperone pathway proteins is altered in pathophysiological states. These changes appear to favor the progression of various types of tumors and Alzheimer's disease. In this context, it is relevant to investigate possible changes in these pathways in a prodromal model of synucleinopathy. Objective: To characterize a model of lipopolysaccharide (LPS)-induced synucleinopathy by investigating the development of behavioral and clinical changes in the prodromal phase, as well as changes in the inflammasome and chaperone pathways. Methods: This is an experimental study of synucleinopathy in a murine model approved by the Ethics Committee on the Use of Animals at UFMG. Mice aged 10-11 weeks were divided into two groups: LPS and Control. The LPS group received the lipopolysaccharide E. coli 0111.4 (Sigma-Aldrich, USA) systemically, in daily doses of 250µg/kg/day, for 7 consecutive days, while the Control Group received 0.9% saline solution under the same conditions. Standardized behavioral tests, real-time expression analysis (RT-PCR) and enzyme-linked immunosorbent assays (ELISA) were performed on samples from the hippocampus, substantia nigra and striatum at two moments. Data were analyzed using the Shapiro-Wilk Test, T Test and Welch T Test, with a significance level of p < 0.05. Results: LPS caused weight loss during the induction period (2nd and 3rd days) and motor behavioral changes until the 4th day after induction (dpi). Animals in the LPS group showed changes in the Barnes Maze and Y-maze tests at 23 dpi, indicating cognitive impairments. Regarding molecular tests, an increase in the expression of total alpha-synuclein was observed on the 4th dpi, in addition to changes in the concentrations of inflammatory mediators and neurotrophic factors at both moments evaluated (4th and 23rd dpi), depending on the brain region evaluated. The mRNA levels of components of the inflammasome and chaperone pathways were also altered after LPS administration. Conclusions: The LPS model of synucleinopathy demonstrated to be a potential model for the study of prodromal changes, potentially mediated by alterations in the chaperone and inflammasome pathway. These changes appear to be brain region and time dependent. Keywords: Synucleinopathies, Parkinson' disease, inflammasome, chaperones, animal model, lipopolysaccharide.